The PPARγ Agonist Rosiglitazone Is Antifibrotic for Scleroderma Lung Fibroblasts: Mechanisms of Action and Differential Racial Effects - Galina S. Bogatkevich; Kristin B. Highland; Tanjina Akter; Richard M. Silver (Pulmonary Medicine)
We present novel data demonstrating that the expression of PPARγ is reduced in lung fibroblasts from black SSc-ILD patients as compared to white patients. Activating PPARγ with the agonist rosiglitazone increased the expression of MMP-1 and inhibited collagen type I in lung fibroblasts isolated from white, but not black, SSc-ILD patients. Blocking the c-Met receptor abolishes rosiglitazone's effects on collagen and MMP-1 in lung fibroblasts isolated from white SSc-ILD patients, while augmenting the expression of the c-Met receptor in fibroblasts from black SSc-ILD patients replicates the effects of rosiglitazone seen in whites. We conclude that PPARγ agonists warrant consideration as potential antifibrotic drugs in patients with SSc-ILD. Differential therapeutic effects might be anticipated especially relative to racial differences and the functional expression of the c-Met receptor.